ЕЛЕКТРОМАГНІТНІ ПРОЦЕСИ У ДЕМПФЕРНІЙ СИСТЕМІ РОТОРІВ ГІДРОГЕНЕРАТОРІВ ПРИ НЕРІВНОМІРНОСТІ ПОВІТРЯНОГО ПРОМІЖКУ - Васьковський, Ю.М.; Цивінський, С.С.; Титко, О.І. (Інститут електродинаміки НАН України, Київ, 2015)
With prolonged use of powerful hydro generators appears uneven air gap between the stator and rotor. It resulting in pulsation of the magnetic flux in the rotor poles, and in the rotor bars flow induced currents. The distribution of induced current between the rods is uneven. It’s causing extensive thermo mechanical deformations of the rods and appears pulsating electromagnetic forces, acting on rods. Known technical measures for maintaining uniformity of air gap in hydro generators are not effective. Therefore it is necessary improvements of the system rods of rotor of hydro generators to enhance its resilience. A new mathematical model was worked, the physical processes were analyzed and the main causes of damage of the rotor damper system with the presence of the rotor eccentricity were researched. A number of technical solutions for significantly reducing the negative thermo mechanical deformations and pulsating forces in the rotor rods was proposed. References 6, figures 5.